PENERAPAN METODE ZIYADAH DAN MUROJA’AH TERHADAP KUALITAS HAFALAN SANTRI AKHWAT DI PESANTREN QUR’AN AL-FIDA KOTA BENGKULU - Sabillah Nur Fadillah; Edi Ansyah; Adam Nasution (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2026)
This study aims to describe the implementation of the Ziyadah and Muroja’ah methods and to analyze the impact of their integration on the memorization quality of female students at Pesantren Qur’an Al-Fida Kota Bengkulu. The research focuses on three main aspects: the mechanism of implementing Ziyadah in improving recitation accuracy, the strategies of Muroja’ah in maintaining memorization, and the overall effect of integrating both methods on the quality of tahfidz.This study employed a qualitative approach with a descriptive research design. Data were collected through participatory observation of daily tahfidz activities, in-depth interviews with caregivers, instructors, and female students, as well as documentation review of memorization records. Data analysis was conducted through data reduction, data display, and conclusion drawing. The validity of the data was ensured through source and method triangulation to maintain credibility and objectivity.The findings reveal that: (1) the Ziyadah method is implemented through tahsin guidance prior to memorization, the establishment of daily targets, and intensive repetition (tikrar) to ensure accurate tajwid application in newly memorized verses; (2) the Muroja’ah method is carried out regularly and systematically through independent revision, paired recitation sessions (sima’i), and periodic evaluations before instructors to maintain fluency and long-term retention; and (3) the balanced integration of Ziyadah and Muroja’ah effectively improves students’ memorization quality. The analysis indicates that the synergy of both methods results in greater fluency, more accurate application of tajwid rules, and stronger memorization stability (itqan). The study concludes that maintaining a balance between adding new memorization and preserving previous memorization is essential to achieving an ideal standard of tahfidz quality among female students